PENGARUH KOMPETENSI KARYAWAN DAN KEMAMPUAN TEKNIS PERSONAL TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI KOMPUTERISASI PT. PELABUHAN INDONESIA II (PERSERO) CABANG BENGKULU - Elviza Diana (Universitas Prof.Hazairin,SH Bengkulu, 2020)
Accounting information system users play an important role in the progress of a company because accounting information system users can encourage the performance of information systems for the better. Information system performance runs well if users can understand, use, and apply technology to become useful information for decision making so that company goals can be met and personal performance can be assessed as good. From the calculation of the significance value for the Employee Competency variable, it shows a value below the significance level of 0.05 and the t-count value of 2.763> t-table of 2.109 means that H1 is accepted so that the Employee Competence has a significant effect on the Computerized AIS Performance at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch. The results of the F test show that the Employee Competence and Personal Engineering Ability have a Fount of 17.498 with a significance value of 0.000, this means the significance level is <0.05 and the F-count is 13.330> F-table 3.59 which means that H3 is accepted, it can be concluded that the Employee Competence and the ability of personal engineering simultaneously has a significant effect on the performance of the computerized accounting information system at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch.